2013
DOI: 10.1177/1420326x13499173
|View full text |Cite
|
Sign up to set email alerts
|

Performance testing of engineering controls of airborne infection isolation rooms by tracer gas techniques

Abstract: The ventilation performance of airborne infection isolation rooms (AIIRs) was assessed in three Finnish hospitals by examining the air change rate, contaminant removal efficiency and leakage of contaminants outside the isolation room by using tracer gas techniques. Results showed that infectious agents can escape from the AIIR during egress despite high ventilation rates in the AIIR and anteroom (air change rate, 4–24 h−1) and the pressure difference between the AIIR and corridor was −0.2 to −29 Pa. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In the closely related baseline study performed without ventilation, Kal-liom€ aki et al [20] found out that moving against the opening direction of the single hinged door, the passage amplified the doorway flows resulting in a higher air volume transfer across the doorway compared to the other passage direction. However, Hayden et al [18] and Kokkonen et al [25] did not find any significant effect of the passage direction on the air volume migration across the isolation room doorway when realistic ventilation rates were used. Fig.…”
Section: The Effect Of Simulated Human Passagementioning
confidence: 93%
See 1 more Smart Citation
“…In the closely related baseline study performed without ventilation, Kal-liom€ aki et al [20] found out that moving against the opening direction of the single hinged door, the passage amplified the doorway flows resulting in a higher air volume transfer across the doorway compared to the other passage direction. However, Hayden et al [18] and Kokkonen et al [25] did not find any significant effect of the passage direction on the air volume migration across the isolation room doorway when realistic ventilation rates were used. Fig.…”
Section: The Effect Of Simulated Human Passagementioning
confidence: 93%
“…Enhanced usage has led to increased interest in containment testing and to door operation induced air and contaminant transport [19e34]. A wide variety of different methods have been used to study the issue, including: computational fluid dynamics (CFD) [23,26,30e32,34], small-scale models [19,22,24,29], full-scale models [20] and field studies [21,25,27,28,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…A pressure outlet at –10 Pa is used for the outlets. The tracer gas (i.e., contaminants) is assumed to be released from the heads of the patients in the ward [24] , [44] . Based on the literature, given the most unfavorable conditions for the environment of medical staff in an isolation ward, the rate of contaminants generated is 0.7 L·s -1 under steady conditions [45] , [46] and 10 L·s -1 for 2 s with a frequency of 40 counts per hour under unsteady conditions [47] , [48] , [49] .…”
Section: Methodsmentioning
confidence: 99%
“…In different national regulations and the World Health Organization (WHO) recommendations, ACHs range from 6 to 15 h –1 [12] , [18] , [19] , [20] , [21] , [22] , [23] . Field test studies have also shown that new isolation rooms do not always comply with an ACH of 12 h–1, and as many as 21% (3/14) of tested isolation rooms violated the lowest requirement of 6 h –1 for existing buildings [24] . Lower ACHs are used in order to conserve energy [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…They found that increasing pressure differentials reduced the door opening and care provider movement induced contaminant transfer across the doorway. Kokkonen et al (2014) carried out performance testing of airborne infection isolation rooms (AIIRs) by tracer gas techniques in real hospital settings. They found that up to 1.7 m 3 of air can migrate to an anteroom during door opening and movement of a HCW through the doorway.…”
Section: Experimental Studies On the Exchange Flows Through Doorwaysmentioning
confidence: 99%